2021
DOI: 10.1088/1674-4926/42/8/082802
|View full text |Cite
|
Sign up to set email alerts
|

Impact of switching frequencies on the TID response of SiC power MOSFETs

Abstract: Different switching frequencies are required when SiC metal–oxide–semiconductor field-effect transistors (MOSFETs) are switching in a space environment. In this study, the total ionizing dose (TID) responses of SiC power MOSFETs are investigated under different switching frequencies from 1 kHz to 10 MHz. A significant shift was observed in the threshold voltage as the frequency increased, which resulted in premature failure of the drain–source breakdown voltage and drain–source leakage current. The degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In previous studies, total ion dose (TID) and single event effect (SEE) were usually studied separately. [7][8][9] The TID effect has been studied in terms of irradiation conditions, such as temperature [10][11][12] and gate bias. [13][14][15] It has been revealed that the TID effect is induced by the radiation-induced holes moving toward the SiC/SiO 2 interface and trapped by defects in the oxide near the interface.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, total ion dose (TID) and single event effect (SEE) were usually studied separately. [7][8][9] The TID effect has been studied in terms of irradiation conditions, such as temperature [10][11][12] and gate bias. [13][14][15] It has been revealed that the TID effect is induced by the radiation-induced holes moving toward the SiC/SiO 2 interface and trapped by defects in the oxide near the interface.…”
Section: Introductionmentioning
confidence: 99%